The modernization of the educational system in France: the New Public Management between the affirmation of the State and the decentralized government - Derouet, Jean-Louis (Revista Brasileira de Política e Administração da Educação - Periódico científico editado pela ANPAE, 2017)
This text examines the process of modernization of the Educational System in France. It aims to understand the affirmation of the State and the decentralized government in the context of the discussion of the New Public Management. It examines the legacies, narratives, and policies of modernization, as well as the paradoxes of the new French public administration in education. It is questioned if the New Public Management was, in fact, implemented in the French educational system. It is stated that, in education, only administrative and financial responsibility entered the institutions without making many consequences on the work of teachers. The main teachers and supervisors are signing contracts and developing evaluations and audits, but the bureaucratic structure still prevails. It is understood, however, that a third way, between the State and the market, is being sought, especially regarding decentralization, with the emphasis on the most shared local responsibilities and the possible changes in the status of civil servants.